Techniques on dispersion of nanoparticles in polymer matrices: a review - Nasrudin, Nurul Reffa Azyan; Mazlan, Norkhairunnisa; Tay, Chai Hua; Mohamed Ariff, Azmah Hanim (Universiti Putra Malaysia Press, 2017)
Dispersibility of nanoparticles is the key problem in nanotechnology industries, and thus warrants attention on the techniques of dispersion. This review paper presents dispersibility of treated nanoparticles in polymer resin. Dispersibility of nanoparticles in polymer media is crucial in order to enhance the mechanical and thermal properties of nanocomposite. This paper concentrates on several preparations on how to incorporate nanoparticles in polymer to overcome the problem described in this review. A few techniques are discussed in this paper such as by using ultra sonication or even directly mixing nanoparticles into polymer matrix.